2020
DOI: 10.21894/jopr.2020.0080
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment for the Production of Palm Biodiesel

Abstract: A gate-to-gate life cycle assessment (LCA) for the production of palm biodiesel was performed. The LCA study was conducted using SimaPro software version 8.5, and the impact assessment was performed according to ReCiPe 2016 methodology. A three-year (2015-2017) inventory data was obtained from five commercial palm biodiesel producers in Malaysia. Methanol, acids and sodium methoxide (catalyst) were identified as three major contributors to the environmental impacts. Impact assessment showed that replacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Few studies in the literature have attempted to estimate the greenhouse gas (GHG) emissions for CPO production in Malaysia. For instance, Subramaniam et al [ 9 ] analysed the GHG emissions from 12 palm oil mills in Malaysia with capacities ranging from 40 to 90 t/h. The average GHG emissions observed is 987.18 kg CO 2 -eq/t CPO.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies in the literature have attempted to estimate the greenhouse gas (GHG) emissions for CPO production in Malaysia. For instance, Subramaniam et al [ 9 ] analysed the GHG emissions from 12 palm oil mills in Malaysia with capacities ranging from 40 to 90 t/h. The average GHG emissions observed is 987.18 kg CO 2 -eq/t CPO.…”
Section: Literature Overviewmentioning
confidence: 99%
“…It is worth noting that both works did not account for emissions related to plantations and palm-based biomass degradation at mill. This gap was addressed by Subramaniam et al [ 9 ], whose analysis showed the total GHG emissions when none of palm-based biomass is recovered can be as high as 3584.05 kg CO 2 -eq/t CPO.…”
Section: Literature Overviewmentioning
confidence: 99%
“…The cultivation policy implemented by oil growers in Cameroon as in all producing countries aims to increase production yield in order to satisfy high demand, which leads them to use enormous quantities of chemical fertilizers in their practices fertilization. According to [6], the application of nitrogen fertilizers is the primary source of greenhouse gas emissions in plantations. In addition, some of these fertilizers are responsible for the pollution of surface water and groundwater.…”
Section: Introductionmentioning
confidence: 99%